Assessment of Firearm Injuries (FAIs) Based on Gender and Age: A Single Center Study - Abdul Samad, Ishrat Bibi, Naseem Akhter, Shahla Imran, Aisha Khalid, Jamshed-Ul-Qadir Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the frequency of firearm injuries between gender and age from tertiary care hospital of Nawabshah, Sindh, Pakistan. Methodology: This descriptive retrospective study was carried at Medicolegal section of Peoples Medical College Hospital and Department of Forensic Medicine & Toxicology, Peoples University of Medical & Health Sciences, Nawabshah District Shaheed Benazirabad, Sindh, Pakistan from 1st January 2021 to 31st December 2021. A total of 216 patients data were analyzed via purposive sampling method. The consent was also taken from the hospital to access the patients’ record. The data were collected on pre-designed sheet based on objective without any gender and age difference. Results: One hundred and sixty one (74.5%) were males while remaining 55(25.5%) belonged to females and 42(19.44%) patients belonged 20-25 years of age. Ninety eight (45.37%) had affected head injury, 42(19.44%) had affected face injury, 37(17.13%) had affected abdominal injury, 39(18.05%) had affected hind limb injury. Practical implication: The practical implication of the study was to aware the current trends of the FAI based on gender and age. Therefore we are more vigilant towards the diagnosis and treatment strategies. Conclusion: Most of the firearm injuries were present in male due to more authority and will power as compared to female. Further mostly the age was from 20-25 years because in this age the persons are not so much mature. Another result was also assessed that most of the mortalities are due to head injury. Keywords: Firearm injuries, Gender, Age, Forensic medicine, Sindh, Pakistan